Low back pain and risk factors among Taxi drivers in Turkey: a cross-sectional study - Kurtul, Seher; Güngördü, Nejdiye (La Medicina del Lavoro, 2022)
Background: Taxi drivers have an increased risk of low back pain due to both physical and occupational conditions. This study aims to determine the prevalence of low back pain and occupational risk factors among taxi drivers working in İzmir, Turkey. Methods: This study was conducted with 447 taxi drivers at randomly selected taxi stands between April and September 2021. The questionnaire included demographic, individual, and work-related questions; the Nordic Musculoskeletal Questionnaire; and the Back Pain Functional Scale (BPFS). Results: The prevalence of low back pain in the last year was 49.7%. In multivariate logistic regression analyses, the risk factors for low back pain included having a body mass index of 25-29.9 kg/m2 (OR= 1.67, 95% CI 1.01-2.76) or ≥30 kg/m2 (OR= 2.15, %95 CI 1.19-3.87), no physical activity (OR= 1.66, 95% CI 1.06-2.62), years of work >10 (OR= 3.23, 95% CI 1.89-5.53), no weekly rest period (OR= 3.11, 95% CI 1.42-6.81), having no lumbar support on the driver's seat (OR:1.67, 95% CI:1.05-2.66), or undecisive job satisfaction (OR= 2.07, 95% CI 1.17-3.66). Being undecided about job satisfaction (OR= 2.34, 95% CI 1.15-4.92) and not having physical activity (OR= 2.10 CI 1.08-4.08) were found to be risk factors for reduced BPFS scores. Conclusion: A strong correlation was found between the frequency of low back pain and the BPFS score and occupational factors. Early detection and management of low back pain are critical to avoid increased low back pain and related injuries among taxi drivers.